Sintilimab-induced intestinal obstruction and hemorrhage of the digestive tract: a case report - Hao, Qian; Zhu, Wenwen; Guo, Qingqing; Lu, Xiuxiu; Zhang, Shijun; Yang, Jianjun; Song, Zhonghua (Frontiers in Immunology, 2025)
Immune checkpoint inhibitors (ICIs) have become an important part of malignant tumor therapy. However, some adverse reactions follow ICIs therapy. The incidence of immune-mediated colitis (IMC) has also increased. Here, the case of a 67-year-old male patient with stage IVB esophagogastric junction squamous cell carcinoma after chemotherapy, targeted therapy and immunotherapy is presented. This patient underwent treatment with six courses of protein-bound paclitaxel + cis-platinum+ sintilimab, followed by maintenance therapy with sintilimab alone. The patient developed intestinal obstruction, abdominal pain, hemorrhage of the lower digestive tract and other discomfort and was diagnosed with multiple jejunal ulcers via colonoscopy and pathological biopsy. The aims of presenting this case report are to improve clinicians’ understanding of and ability to treat sintilimab-related adverse reactions and to more scientifically and rationally administer sintilimab for the treatment of malignant tumors.